Bonding, Bridging and Linking: Involvement of Former Convicts in the Management of Terrorism Countermeasures Strategies - Rahim, Rangga Ardan; Nugraha, Rachmat Fajri Adi (Almana : Jurnal Manajemen dan Bisnis, 2024)
This research aims to analyze how former convicts can contribute to the strategic management of countering criminal acts of terrorism. This research uses the concepts of bonding, bridging, and linking as dimensions of social capital offered by Robert Putnam (2020). Data processing was carried out using in-depth interviews supported by observations of the convict development program. This research shows that former convicts can create a sense of togetherness and group identity, understand alternative narratives in religion and society, and build positive relations with the state as an organization among other convicts. From this research, it is concluded that the involvement of former convicts in the deradicalization program has a positive impact, so its implementation needs to be mainstreamed in implementing the deradicalization program.